Chronological and Skeletal Age in Relation to Physical Fitness Performance in Preschool Children - Ke, Dandan; Lu, Dajiang; Cai, Guang; Wang, Xiaofei; Zhang, Jing; Suzuki, Koya (Frontiers in Pediatrics, 2021)
Introduction: Physical fitness is an adaptive state that varies with an individual’s growth and maturity status. Considering that the difference in skeletal maturity already existed among preschool children, this study was designed to determine the influence of skeletal age and chronological age on preschoolers’ physical fitness performance. Methods: This cross-sectional study was conducted in 945 healthy preschoolers (509 males, 436 females) aged between 3.0 and 6.0 years in Shanghai, China. We used the method of TW3-C RUS to determine skeletal age. Chronological age was measured by subtracting the date of birth from the test date. Sit and reach, 2×10 m shuttle run test, standing long jump, tennis ball throw, 5 m jump on both feet, and balance beam walk were considered for physical fitness performance. Correlation coefficients and partial correlations adjusting height and weight were used to determine the relationships among the variables of skeletal age/ relative skeletal age, chronological age/relative chronological age, and physical fitness items. Results: Skill-related physical fitness was weakly to moderately associated with skeletal age (the absolute value of r: 0.225–0.508, p<0.01) and was moderately to strongly associated with chronological age (the absolute value of r: 0.405–0.659, p<0.01). Health-related physical fitness items (BMI and sit and reach) showed a fairly weak to no correlation with skeletal age and chronological age. After adjusting the height and weight, an extremely weak to no correlation was observed between skeletal age and both health- and skill-related physical fitness, and weak-moderate correlations were noted between chronological age and skill-related physical fitness (the absolute value of r: 0.220–0.419, p<0.01). In children in Grade 1, skill-related physical fitness (except for balance beam walk) showed a weak to moderate correlation with relative chronological age (the absolute value of r: 0.227–0.464, p<0.05). Conclusion: 1) both skeletal age and chronological age are associated with skill-related rather than health-related physical fitness performance, and after adjusting height and weight, chronological age, rather than skeletal age, is associated with skill-related physical fitness performance; 2) for preschool children, skill-related physical fitness performance is influenced by relative chronological age rather than individual differences in skeletal maturation, especially in the lower grades.